Dosimetric Comparison of Dynamic Conformal Arc Therapy and Volumetric Modulated Arc Therapy using Stereotactic Radiotherapy for Carcinoma Brain - Suhani Pinto; Shreekripa Rao; RECHAL DSOUZA; Srinidhi Chandraguthi; Umesh Velu (Iranian Journal of Medical Physics)
Introduction: Stereotactic radiosurgery (SRS) conventionally relies upon dynamic conformal arc therapy (DCAT), yet the untapped potential of volumetric modulated arc therapy (VMAT) has not undergone comprehensive scrutiny. This investigation seeks to bridge this research lacuna by comparing DCAT and VMAT in the context of four-fraction SRS for single brain carcinoma treatment.Material and Methods: A retrospective cohort of twenty patients with solitary brain tumors was meticulously chosen, and treatment plans using both VMAT and DCAT were devised for each case utilizing congruent CT images. The comparative study analysed factors such as target conformity, monitor units and doses to organs at risk.Results: VMAT plans notably exhibited enhanced conformity indices with mean and standard deviation values for the Paddick Conformity Index being 0.650 ± 0.18 for DCAT and 0.751 ± 0.08 for VMAT. Also, VMAT reduced radiation doses to pivotal anatomical structures, in contrast to the DCAT plans. However, the VMAT approach necessitated a greater number of Mus than DCAT with the mean and standard deviation being 986.95 ± 146.3 and 571.36 ± 59.6, respectively.Conclusion: In the realm of SRS for isolated brain carcinoma, VMAT decidedly surpassed DCAT in target conformity as well as in mitigating the risk of brain radiation necrosis. Nonetheless, DCAT find relevance in patients with compromised performance status to prolonged radiotherapy sessions due to its abbreviated duration in the treatment. This research highlights the nuanced considerations inherent in treatment selection and also sheds insightful light on the optimal therapeutic approach.